Avaliação econômica de bibliotecas: uma análise para as Bibliotecas do CAEN e LABOMAR na UFC - Aquino, Mônica Correia (2014)
The library, as it is an intangible good, it is difficult to be measured and its benefits are not captured by the analyses of generated revenues.In the face of this, the work has as theme to identify the economic value of the CAEN and LABOMAR libraries at Federal University of Ceará, which was gauged from the preferences of individuals , which result from their proper interests. The work is a brief history of the studied libraries. For getting this aim, the work brings an approach about the Contingent Valuation Method(MVC) and willingness to pay (DAP) and, from the questionnaires applied between April and June of 2014 with users from the respective libraries, it was possible to check that the average value of DAP for the CAEN library was of R$ 5,23, while that one for the LABOMAR library got R$ 8,96 monthly.